Crop per drop of diesel?: Energy squeeze on India's smallholder irrigation - Shah, Tushaar (2007)
India's smallholder irrigation is in the grip of an energy squeeze and is proving the proverbial last straw on the camel's back. Marginal farmers and sharecroppers are particularly badly hit. Typically, they depend on pump owners for renting pumps, and even as prices have stayed put, the rental rates have risen in tandem with every diesel price hike because of the monopoly power of pump owners in these localised, village-level, informal oligopolies. Pump rentals have also tended to be downwardly sticky - they rise when diesel prices jump but stay put when fuel prices fall. This paper synthesises the results of 15 village studies to understand the impact of the energy squeeze and explores the desperate responses smallholders are forging to cope with or absorb the energy shock, and somehow stay in irrigated agriculture.